Comparative Analysis of ESG Practices and Financial Performance in Public and Private Banks in Indonesia - Nasha Aurellya Putri; Istiono (CITACONOMIA, 2026)
This study examines the implementation of Environmental, Social, and Governance (ESG) practices and their relationship with financial performance in public and private banks in Indonesia. As stakeholder expectations regarding sustainability and corporate responsibility increase, ESG has become an important consideration in the banking sector. A qualitative descriptive approach was employed using secondary data from annual reports and sustainability reports published between 2021 and 2023. The study focuses on four major Indonesian banks: Bank Mandiri, Bank Rakyat Indonesia, Bank Central Asia, and Bank CIMB Niaga. Data were analyzed through content and comparative analysis. The findings show that both public and private banks actively implement ESG practices, although with different priorities. Public banks emphasize sustainable financing, financial inclusion, and community development, while private banks focus on operational efficiency, digital transformation, and customer-oriented strategies. ESG implementation is associated with stable financial performance, stronger stakeholder trust, and improved corporate reputation. The study concludes that ESG integration supports long-term sustainability and competitiveness in the Indonesian banking sector.